Determinação de contaminantes em óleo diesel por ICP-OES empregando a microextração líquido-líquido dispersiva em fase reversa - Delpino, Isabela Solana (2017)
This research developed a method for employing a reversed-phase dispersive liquidliquid microextraction (RP-DLLME) as sample preparation for the extraction and preconcentration of Al, Cd, Cu, Fe, Mn, Ni and Zn in biodiesel samples. The determination of analytes were executed through inductively coupled plasma optical emission spectrometry (ICP-OES). The extraction/pre-concentration step of the analytes was performed using a mixture of two solvents, a dispersing and an extractor, which were added directly to the heated sample. Subsequently, for separation of the phases, the solutions were centrifuged and the sedimented phase was withdrawn to determine the analytes by ICP-OES. For the development of the method was used the experimental planning and optimization of processes, where initially a fractional factorial design was used and then a central composite rotatable design. The variables studied were temperature of the extraction (60, 70 and 80 oC), sample mass (5, 10 and 15 g), volume of extraction phase (0.5, 1 and 1.5 mL), concentration of the extraction (1.5 and 2 mol L-1) and the proportion of the dispersant in the extractive solution (60, 70 and 80%). Quantitative results were obtained using the following conditions: i) temperature of the extraction: 70 oC, ii) sample mass: 8.5 g, iii) volume of extraction phase: 1 mL, iv) concentration of HNO3: 2 mol L-1, and v) proportion of dispersant: 70% (v / v). All experiments were performed using the addition of 1.0 μg g-1 of Al, Cd, Cu, Fe, Mn, Ni and Zn directly in the diesel samples, was used a standard multi-element Conostan® lubricant oil (100 mg L-1). The results were expressed as analyte recovery (%). The calibration solutions were made in aqueous solution and the extracts were directly determined by ICP-OES. The quantification limits (LQ) for Al, Cd, Cu, Fe, Mn, Ni and Zn were 0.0492, 0.0031, 0.0031, 0.0140, 0.0008, 0.0049 and 0.0093 μg g-1, respectively. Accuracy was assessed by addition of analytes. Quantitative recoveries were obtained for all analytes and the relative standard deviations were less than 6.4%. The method was applied to 6 samples of commercial diesel oil, S-10 and S-500, and Al, Fe and Zn were determined in the range of 0.026 to 0.150 μg g-1, the remaining analytes were below the LQ of the method. The method developed using RP-DLLME and determination by ICP-OES presented with adequate precision and accuracy for the determination of Al, Cd, Cu, Fe, Mn, Ni, Zn in diesel oil in low concentrations, minimizing reagent consumption and, consequently the generation of toxic wastes, in a fast and simple way, and is suitable for routine analysis.